Danhong Injection Attenuates Cerebral Ischemia-Reperfusion Injury in Rats Through the Suppression of the Neuroinflammation - Du, Haixia; He, Yu; Pan, Yuanjiang; Zhao, Mengdi; Li, Zhiwei; Wang, Yu; Yang, Jiehong; Wan, Haitong (Frontiers in Pharmacology, 2021)
Neuroinflammation is one of the major causes of damage from central nervous system (CNS) and plays a vital role in cerebral ischemia pathogenesis, which can result in long-term disability and neuronal death. Danhong injection (DHI), a traditional Chinese medicine injection, has been applied to the clinical treatment of cerebral stoke for many years. In this study, we investigated the protective effects of DHI on cerebral ischemia-reperfusion injury (CIRI) in rats and explored its potential anti-neuroinflammatory properties. CIRI in adult male SD rats was induced by middle cerebral artery occlusion (MCAO) for 1 h and reperfusion for 24 h. Results showed that DHI (0.5, 1 and 2 mL/kg) dose-dependently improved the neurological deficits, alleviated cerebral infarct volume and histopathological damage of the cerebral cortex caused by CIRI. Moreover, DHI (0.5, 1 and 2 mL/kg) inhibited the mRNA expressions of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), intercellular cell adhesion molecule-1 (ICAM-1), cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) in ischemic brains, down-regulated TNF-α, IL-1β and monocyte chemotactic protein-1 (MCP-1) levels in serum, and reduced the neutrophil infiltration (myeloperoxidase, MPO) in ischemic brains, in a dose-dependent manner. Immunohistochemical staining results also revealed that DHI dose-dependently diminished the positive expressions of ICAM-1 and COX-2, and suppressed the activation of microglia and astrocyte (ionized calcium-binding adapter molecule 1, Iba-1 and glial fibrillary acidic protein, GFAP) in the cerebral cortex. Western blot analysis showed that DHI significantly down-regulated the phosphorylation levels of the proteins in nuclear factor κB (NF-κB) and mitogen-activated protein kinas (MAPK) signaling pathways in ischemic brains. These results indicate that DHI exerts anti-neuroinflammatory effects against CIRI, which contribute to the amelioration of CNS damage.